PERLUNYA PEMBELAJARAN BAHASA BALI YANG REKREATIF DI SEKOLAH DASAR MULTIKULTURAL DAN MULTILINGUAL - Ni Made Dhanawaty (Madah: Jurnal Bahasa dan Sastra, 2013)
Balinese, the indigenous language of Bali, is taught as a local content subject at schools (especially at primary schools) in Bali. Since, it is being part of educational curriculum, Balinese is not only learned by it’s native speaker students but also learned by multicultural and multilingual students,particularly in cities. In fact, the Balinese is not very attractive to non-native students because it is not the first nor the second language of them and it is not play any important roles in their daily life. This tendency cause the students show a lower competence in Balinese subject. In order to improve the students competence in Balinese subject, especially communicative competence, it is deemed to suggest a method of recreational learning process that make students have an interest to the subject and enjoy the learning process of the subject so that they are motivated to learn the subject as well as to succed in it. This article proposes the importance of recreational learning method, in this matter, learning by using story completed with role play, learning by using songs and music, and learning by doing group activities and games. This model is also effective to improve children’s characters. Bahasa Bali, yang merupakan bahasa penduduk asli Bali, diajarkan di sekolah-sekolah (terutama sekolah dasar) di Bali sebagai muatan lokal1. Karena menjadi bagian dari kurikulum pendidikan, pelajaran bahasa Bali juga dipelajari oleh para siswa multikultural dan multilingual, terutama di daerah perkotaan. Pembelajaran bahasa Bali umumnya kurang diminati oleh siswa non-penutur bahasa Bali karena, pertama, bahasa Bali bukan merupakan bahasa pertama dan kedua, bahasa Bali tidak terlalu menjadi tuntutan dalam kehidupan mereka. Ketiadaan minat itu berujung pada kurangnya kompetensi berbahasa Bali siswa. Untuk meningkatkan kompetensi siswa, khususnya kompetensi komunikatifnya, dipandang perlu menggagas proses pembelajaran yang rekreatif, yang membuat siswa tertarik dan menikmati proses pembelajaran sehingga mereka termotivasi untuk belajar dengan baik dan berhasil baik. Tulisan ini mengetengahkan pentingnya metode pembelajaran yang bersifat rekreatif, dalam hal ini pembelajaran melalui cerita, lengkap dengan bermain peran, pembelajaran melalui lagu dan musik, dan pembelajaran melalui aktivitas kelompok dan permainan. Model ini juga sangat efektif untuk meningkatkan karakter anak.